Kajian Hukum terhadap Tindak Pidana Kampanye Hitam di Media Elektronik berdasarkan Perspektif Pemilihan Umum di Indonesia (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the legal regulations on black campaign crimes in electronic media from the perspective of general elections in Indonesia. The research method used is normative juridical with a statutory, case, and conceptual approach. The results of the study indicate that the legal regulations on black campaigns in electronic media in elections in Indonesia are not yet firm and responsive to developments in information technology. Although the Election Law (Law No. 7/2017 in conjunction with Law No. 7/2023) prohibits insults, defamation, and the spread of slander by implementers, participants, and official campaign teams, this provision does not explicitly cover black campaigns by other parties in electronic media. The absence of the phrase "black campaign" in positive law leads to vague interpretations. The Electronic Information and Transactions Law (UU ITE) (UU No. 11/2008 in conjunction with Law No. 1/2024) which can ensnare the spread of hatred and hostility is general and not specific to the context of elections. The disharmony and overlap between the Election Law and the ITE Law result in legal uncertainty. The handling of this crime is hampered by aspects of legal substance that have not yet clearly defined black campaigns, their scope, and sanctions. Structural obstacles include ineffective coordination between institutions (Bawaslu, Police, Prosecutors in the Gakkumdu Center), overlapping authority, differences in interpretation, and limitations in human resources and technology to track anonymous perpetrators. From the aspect of legal culture, there is still a permissive attitude of the community towards negative information, a lack of awareness of political ethics, and the indecisiveness of law enforcement officers, especially if it involves influential political actors. In addition, it is recommended to strengthen the capacity of legal structures, improve the legal culture of the community through digital literacy and political education, and improve the performance of law enforcement officers who are professional, brave, fair, and transparent.